Genome-wide scan reveals divergent selection among taurine and zebu cattle populations from different regions - Edea, Zewdu; Dadi, H.; Dessie, Tadelle; Uzzaman, M.R.; Rothschild, Max F.; Kim, E.S.; Sonstegard, T.S.; Kim, K.S. (Wiley, 2018)
In this study, to identify genomic signatures of divergent selection, we genotyped 10 cattle breeds/populations (n = 275), representing eight Ethiopian cattle populations (n = 229) and two zebu populations (n = 46) adapted to tropical and sub‐tropical environments, using the high‐density single‐nucleotide polymorphisms (SNPs) derived mainly from Bos indicus breeds, and using five reference taurine breeds (n = 212). Population genetic differentiation (FST) values across sliding windows were estimated between zebu and reference combined taurine breeds. The most differentiated regions (FST ≥ 0.53), representing the top 1% smoothed FST values, were considered to represent regions under diversifying selection. In total, 285 and 317 genes were identified in the comparisons of Ethiopian cattle with taurine and Asian zebu with taurine respectively. Some of these genes are involved in stress responses/thermo‐tolerance and DNA damage repair (HSPA4, HSF1, CMPK1 and EIF2AK4), pigmentation (ERBB3 and MYO1A), reproduction/fertility (UBE2D3, ID3 and PSPC1), immune response (PIK3CD and AKIRIN2) and body stature and size (MBP2, LYN and NPM1). Additionally, the candidate genes were associated with functional terms (e.g. cellular response to stress, DNA repair, inflammatory response) important for physiological adaptation to environmental stresses. The results of our study may shed light on the influence of artificial and natural selection in shaping the genomic diversity of modern cattle breeds and also may serve as a basis for further genetic investigation of traits of tropical adaptation in cattle.